2002
DOI: 10.1016/s0736-0266(01)00110-3
|View full text |Cite
|
Sign up to set email alerts
|

The characterization of versican and its message in human articular cartilage and intervertebral disc

Abstract: Splicing variation of the versican message and size heterogeneity of the versican core protein were analyzed in human articular cartilage and intervertebral disc. Splicing variation of the message was studied by PCR analysis to detect the presence or absence of exons 7 and 8, which encode large chondroitin sulfate attachment regions. At all ages in normal cartilage from the third trimester fetus to the mature adult, the presence of the versican isoform possessing exon 8 but not exon 7 ( V , ) could be readily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 39 publications
2
49
1
Order By: Relevance
“…Although previous immunohistochemical studies failed to detect versican in human adult cartilage (3), biochemical studies demonstrated the presence of versican in human articular cartilage from the fetal stage to mature adult (13). An age-associated decrease in versican transcription of the human articular cartilage has also been reported (11).…”
Section: Discussionmentioning
confidence: 99%
“…Although previous immunohistochemical studies failed to detect versican in human adult cartilage (3), biochemical studies demonstrated the presence of versican in human articular cartilage from the fetal stage to mature adult (13). An age-associated decrease in versican transcription of the human articular cartilage has also been reported (11).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, glycosylation further increases their molecular weight, as a result of which they are found in the ECM with sizes ranging from 1000 to 2500 kDa. [98][99][100] Further alternative splicing of the versican gene, which encodes the GAG chain-binding sites, generates ≥4 isoforms with different molecular weights, creating even more variation. These large matrix components interact with other matrix proteins, growth factor, and cell surface receptors.…”
Section: Hyalectans: Versicanmentioning
confidence: 99%
“…2 A high proteoglycan-to-collagen ratio and low aggrecan-toversican ratio can be used to distinguish NP from cartilage. 2,5 MSCs have been shown to undergo chondrogenesis in vitro using a high cell density pellet culture system, [6][7][8] which mimics the cellular condensation requirements for embryonic mesenchymal chondrogenesis and provides the physical and biochemical environmental factors conducive to cartilage formation. 7 Treatment with transforming growth factor b (TGF-b) superfamily members, TGF-b1 7,[9][10][11][12] or TGF-b3, 6,8 and dexamethasone 7,8,13,14 are key requirements for the in vitro chondrogenic differentiation of MSCs.…”
Section: Introductionmentioning
confidence: 99%